Fighting for survival: persons with disabilities’ activism for the mediatisation of COVID-19 information - Mhiripiri, Nhamo Anthony; Midzi, Ratidzo (Media International Australia, 2021)
Crises times have an uncanny way of giving salience to struggles for democracy. The new coronavirus – also known as COVID-19 – became a global public health issue that stirred other democratic concerns from persons living with disabilities who wanted access to health information for their survival. People living with various types of disabilities have special communication and information needs, some of which require specific technologies, formats and language. The pandemic got people concerned about their safety and survival. This article contextualises and critiques US, Britain and Zimbabwean activists representing persons living with disabilities’ reactions to the manner their public authorities availed COVID-19 health messages to disabled constituencies via mainstream television. It compares how suitable was televised content from US, Britain, Zimbabwean and New Zealand stations for the Deaf and Hard of Hearing, before exploring complaints and lawsuits from the disability constituency pertaining to access to COVID-19 health information.